Red blood cell parameters as biomarkers of retinopathy of prematurity in preterm infants born before 30 weeks of gestation - Hajime Maeda; Hayato Go; Hajime Iwasa; Shun Hiruta; Hirotaka Ichikawa; Yukinori Sugano; Kei Ogasawara; Nobuo Momoi; Tetsuju Sekiryu; Mitsuaki Hosoya (Scientific Reports)
Abstract Retinopathy of prematurity (ROP) is a major cause of preventable blindness in preterm infants. The association between red blood cell (RBC) parameters and the development of ROP remains unclear. The objectives of the present study were to evaluate the association between RBC parameters and ROP treatment. This single-center, retrospective cohort study included preterm infants born at < 30 weeks of gestation. Data pertaining to RBC parameters and ROP treatment were obtained from the medical records. A receiver operating characteristic (ROC) analysis was performed to determine the cut-off values of the RBC parameters according to the need for ROP treatment. Multiple logistic regression analyses assessed the association between ROP treatment and RBC parameters at birth and on day of life (DOL) 28. We included 202 infants, and 44.1% were treated for ROP. After adjusting for confounders, we observed associations between ROP treatment and mean corpuscular volume (MCV) values > 117.3 fL at birth (adjusted odds ratio [aOR]:2.3; 95% confidence intervals CI 1.0–5.3). Additionally, on DOL 28, hemoglobin (Hb) values < 9.9 g/dL (aOR:3.0; 95% CI 1.4–6.7), hematocrit (Hct) values < 31.0% (aOR:2.7; 95% CI 1.3–5.6), and red cell distribution width (RDW) values > 18.5% (aOR:2.6; 95% CI 1.1–6.2) were associated with ROP treatment. In conclusion, our study indicated that infants born at < 30 weeks of gestation with an MCV > 117.3 fL at birth, along with Hb < 9.9 g/dL, Hct < 31.0%, and RDW > 18.5% on DOL 28, had an increased risk of requiring ROP, warranting treatment.